Prevalence of neuromyths among psychology students: small differences to pre-service teachers - Novak-Geiger, Verena (Frontiers in Psychology, 2023)
Neuroscience will possibly aid the educational practice but neuromyths are prevalent worldwide. Certain misconceptions about learning, memory and the brain are prevalent in different groups and hard to dispel. Bridging the gap might be too far. However, Psychology may serve as a bridge between these distant fields. The present study examined neuromyth endorsement in psychology students. An online questionnaire based on 20 neuromyths and 20 neurofacts was used. Additionally, neuroscience exposure at university and media exposure was assessed. The sample consisted of psychology students (N=116) in Austria and was compared to a teacher-training sample (Krammer et al. 2019). The different groups were compared using Signal Detection Theory, chi-square test, non-parametric correlation analyses, and independent sample t-test. No correlation between neuroscience exposure at university and leisure time for psychology students at the beginning of their studies could be found. Here, the same misconceptions were among the most prevalent - compared to the teacher-training students sample. Results show significant difference between the groups on discrimination ability and response bias. Although psychology students share the same most prevalent misconceptions, they differ significantly in their amount of agreement. The reported study reveals a better discernment ability and lower response bias on neuromyths in the Psychology students sample. On the individual item level, they performed better at rejecting some neuromyths than pre-service teachers. In conclusion, some neuroscience and pedagogical psychology training improves the ability to discriminate between true and false statements. Therefore, directly addressing these misconceptions within the study program – Teacher Training and Psychology- could reduce neuromyth endorsement.